Effect of the Silver Nanoparticles on the Histology of Albino Mice Ovaries (Baghdad Science Journal, 2025)
The aim of study is to identify the histological changes in ovaries of the albino mice exposed to silver nanoparticles. Sixty adult females were collected and exposures by 4000 p.p.m. and 50-150 nm in size, Females were divided into 3treated groups. The concentration dosage was (1, 1.5 and 2) p.p.m. of silver nanoparticles for 7, 14 and 21 days as exposure periods as well as control group which treated by normal saline. Treated groups appeared different histopathological changes, it is depending on the concentration of silver nanoparticles and the period of exposure. These changes were included congestion in the blood vessels, hemorrhage, hyaline degeneration, fatty degeneration, pyknosis, necrosis as well as fusion of cells in follicular cells, amyloid proteins in the blood vessels and Fatty necrosis.